Mechanical recycling of textile waste - Nemeša Ineta; Pešić Marija; Bozoki Valentina (Tekstilna industrija)
During mechanical recycling several mechanical treatments are used to degrade textile waste and make it ready for new application in different other industries. Mechanical recycling process consists of several work steps. Pre or post-consumer textile waste is firstly cut in small pieces by a shredding machine. Blending boxes with different storage capacities are used to blend cut textile waste. A feeding unit is placed in between a blending box and a tearing machine. Tearing machines separate individual fibers by tearing small pieces of shredded textile material apart. At the end of the textile recycling process the opened fibers are compressed in needed size bundles to store and transport for their further use. Insufficiently sorted waste is the most serious problem that complicates mechanical recycling processes, reduces the quality of recycled fibers. Currently there are not available efficient methods to recycle coated, laminated textiles and materials with elastan. Compared with other recycling methods the mechanical recycling of textile waste has already decades of experience, it is the most developed, most widely used, requires much lower investments and energy resources.